BODY IMAGE SISWA DITINJAU DARI GENDER - Alidia, Fauzana (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2018)
Body image is a description of perceptions, feelings and attitudes about the body as a whole person or a particular the part of body. The differences of body image is influenced by several aspects. Among of them, there is gender. The aims of this research are :1 ) to describe the body image of male students , 2 ) to describe the body image of female students, and 3 ) to find out the body image differences between male students and female students. This research was descriptive research by using quantitative approach. The population of this research was the students of grade XI SMA Negeri Tanjung Mutiara in the period of 2013/2014 (285). Amount of research sample was 56 male students and 110 female students and had been chosen by using simple random technique. The instrument that had been used was Likert scale model. The first and second research purpose were analyzed by using percentage technique, and the third research purpose were analyzed by using t-test. The results of research are: 1) Body image of male students are in the high category, 2) Body image of female students are in the high category, 3) There is a differences between male body image and female body image.